ANALISIS PERILAKU ISLAMI TERHADAP NIAT BELI KOSMETIK HALAL MELALUI SIKAP KONSUMEN - Lisa Adriani; Ma'ruf Ma'ruf (Journal of Management and Business Review, 2020)
The current trend in Indonesian society is the hijrah trend. People change lifestyles to become more aware and concerned with the halal of a product. Halal standard developed from food-beverage products, now it develops service and lifestyle products (halal cosmetics). One of the halal cosmetics sold in Indonesia is the Make Over Cosmetics Brand. Make Over has been registered in the Indonesian Ulema Council as halal cosmetics. The purpose of this research is to analyze directly between the variables of Islamic religion, halal knowledge, halal lifestyle to the purchase intention variable and the indirect effect mediated by the attitude variable. The sampling technique is purposive sampling of 185 respondents. The data analysis technique is quantitative analysis using SMART PLS 3. The results of the analysis show a significant positive effect between Islamic religious variables, halal knowledge, halal lifestyle on direct purchase intention variables and indirectly related through influence variables with partial mediation. Need to be considered, supporting the principle of halal and open-minded to change.